(untitled) (Bangladesh Journal of Medicine, 2026)
Background: Vitamin D (Vit D) is a fat-soluble steroid hormone crucial for skeletal health, immune function, and chronic disease prevention. Despite ample sunlight, a high prevalence of hypovitaminosis D has been reported in Bangladesh. This study aimed to determine the prevalence and correlates of Vit D deficiency(VDD) among adults attending a tertiary care facility in Dhaka. Methods: A crosssectional study was conducted at the Bangladesh Institute of Health Sciences (BIHS) General Hospital, Dhaka, from 1st January 2021 to 31st December 2023. A total of 300 adult patients (N=300) meeting inclusion criteria were enrolled. Data on socio-demographics, lifestyle, and clinical presentation were collected via a structured questionnaire. Serum 25-hydroxyvitamin D [25(OH)D] was measured by Chemiluminescent Microparticle Immunoassay (CMIA). Results: The mean age of participants was 38.7±12.4 years, with 54.0% Female and 46.0% male. Hypovitaminosis D (25(OH)D<30 ng/mL) was present in 276 (92.0%) patients, comprising 179 (59.7%) deficient (<20 ng/mL) and 97 (32.3%) insufficient (20-29.9 ng/mL). Only 24 (8.0%) had sufficient levels. Deficiency was significantly higher in females (66.7%) compared to males (53.7%) (p=0.015), in those with indoor occupation (65.8%) (p=0.001), inadequate sun exposure (67.2%) (p=<0.001), and low fish intake (<2 times/week) (69.0%) (p=<0.001). The predominant presenting complaints were generalized fatigue (67.7%), bone/joint pain (59.3%), and muscle weakness (52.0%). Conclusion: An alarmingly high prevalence of Vit D deficiency was found among adult patients in this urban tertiary care setting. Female gender, indoor lifestyle, inadequate sun exposure, and poor dietary habits were significant risk factors. Public health strategies, including awareness campaigns, dietary fortification, and targeted supplementation, are urgently needed to address this silent epidemic. Bangladesh J Medicine 2026; 37(2): 143-148